In-flight tuning system for the CH-53G helicopter - Arnold, U.T.P.; Fuerst, D. (My University, 2015)
Rotor Track and Balance (RT&B) adjustments manually applied to the rotor on the ground are burdensome, error-prone and time-consuming. Moreover, as often as the rotor properties change for any reason the RT&B procedure must be repeated. Today, the search of an acceptable setting usually requires a sequence of several dedicated check flights in different RT&B flight conditions to verify the effect of those manual changes. Due to the flight-condition-dependent effect of blade dissimilarities and due to the limited number of locations where compensational changes can be applied, the suppression of the 1/rev unbalances can never be perfect across all flight regimes. Therefore, a system designed to adjust the RT&B setting during the flight can significantly improve the over-all vibratory condition of the rotorcraft. In addition, such system considerably reduces the time for RT&B still required today for the repetitive check flights and the manual adjustments. ZF Luftfahrttechnik had been contracted to demonstrate the feasibility of this approach within a dedicated flight test campaign. Core components of the In-Flight Tuning (IFT) system are electrical Smart Pitch Rods (SPR™), which replace the rigid pitch links of each blade. The SPR™s change their length upon digital commands received from a dedicated control computer. Such close-to-production IFT system has been installed onto a CH-53G testbed of the German Armed Forces and was flight tested at the German Military Flight Test Center in Manching. The tests were designed to prove the concept in a realistic environment and have successfully proven autonomous IFT operation based upon adaptive closed loop algorithms. The benefits that were demonstrated during this campaign comprise (1) reduced vibrations compared to the reference case with fixed pitch link settings throughout all flight regimes, (2) compensation of degrading RT&B condition over time, (3) automatic reconfiguration after sudden changes of blade properties, and (4) reduced RT&B effort after initial rotor reassembly, blade exchange and/or control system rigging. It could also be shown that the IFT algorithm was convergent and robust throughout all maneuvers and never lost track even during the most agile flight condition changes.
Keywords: Test & Evaluation